Environmental Sustainability in Livestock Production - Smith, Nolan (International Journal of Livestock Policy, 2024)
Purpose: The general purpose of this study was to analyze environmental sustainability in livestock production. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to environmental sustainability in livestock production. The study provided valuable insights into the complex interactions between livestock production practices and environmental sustainability, highlighting significant challenges such as greenhouse gas emissions, water pollution, biodiversity loss, and land degradation. It emphasized the importance of adopting integrated approaches to mitigate these impacts, stressing the need for transformative changes in livestock production. The study also underscored the role of policy and governance mechanisms in driving sustainable practices and fostering multi-stakeholder collaboration. Urgency was emphasized in addressing environmental sustainability in livestock production to mitigate negative impacts, urging concerted action from governments, industry stakeholders, researchers, and consumers for a sustainable future. Unique Contribution to Theory, Practice and Policy: The Agroecology theory, Socio-Ecological Systems theory and the Sustainable Livelihoods approach may be used to anchor future studies on environmental sustainability in livestock production. The recommendations advocate for the promotion of sustainable livestock production practices, emphasizing techniques like rotational grazing and integrated pest management to minimize environmental degradation. Investing in research and innovation is crucial to developing new technologies for enhanced sustainability, while education initiatives empower farmers with necessary skills. Policymakers are urged to shape regulations and provide incentives for sustainable practices, with collaboration among stakeholders highlighted as essential for addressing environmental challenges effectively. Raising consumer awareness and promoting sustainable consumption patterns further drive positive change throughout the supply chain. In conclusion, a multifaceted approach integrating innovation, policy, education, and collaboration is essential for achieving environmental sustainability in livestock production, ensuring a balance between conservation and development.